2020
DOI: 10.1097/sla.0000000000002832
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an ICU “Bed Ahead” Policy on ED Length of Stay and Patient Outcomes

Abstract: Preassigning 1 ICU for the yet to arrive next injured patient decreases ED dwell times, complications, HLOS, and in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These studies showed that the expedited transfer of critically ill trauma patients to the ICU is associated with decreased morbidity, hospital length of stay, and mortality. 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the expedited transfer of critically ill trauma patients to the ICU is associated with decreased morbidity, hospital length of stay, and mortality. 3…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the expedited transfer of critically ill trauma patients to the ICU is associated with decreased morbidity, hospital length of stay, and mortality. 3 While the benefits are evident, efficient transfer is not prioritized nor standardized in most pediatric trauma centers. To our knowledge, there are no studies in the medical literature about the expedited transfer of critically injured pediatric trauma patients.…”
Section: Introductionmentioning
confidence: 99%